Comparison of the classification ratios of four depression rating scales commonly used in Turkey - Gaye Saltukoğlu; Arkun Tatar (Psychiatry and Clinical Psychopharmacology, 2017)
Objective: According to literature more than 20 depression scales are in use in Turkey. Considering that depression is a popular area of study, it may not seem abnormally unusual that there are so many measuring scales available. However, so many measuring instruments may lead to a problem of different sensitivity levels and raise the question of whether or not all the instruments have the same sensitivity in measuring the particular entity. The purpose of this study is to compare the four commonly used self-report scales adapted into Turkish, namely CES-Depression Scale, Beck Depression Inventory, the Zung Self-Rating Depression Scale, and the Hospital Anxiety and Depression Scale (depression subscale) by cross-validation. Method: These depression scales had been applied to three hundred and forty-one subjects and total scores of the subjects for each scale have been obtained. Next, the sample group was divided into two according to group averages of total scale scores. Normative scores and cut-off scores have not been considered because the study objective was to compare these scales on a theoretical basis. The groups below and above average for each of the four scales have been compared by the ROC curve analyzes. Results: The results showed that the total score of Beck Depression Inventory had been grouped correctly by the Zung Self-Rating Depression Scale at a ratio of 0.871, the Hospital Anxiety and Depression Scale (depression subscale) at a ratio of 0.885, and by CES-Depression Scale at a ratio of 0.874. The total score of CES-Depression Scale had been correctly grouped by Beck Depression Inventory at a ratio of 0.871, the Zung Self-Rating Depression Scale at a ratio of 0.869, and by the Hospital Anxiety and Depression Scale (depression subscale) at a ratio of 0.862. The total score of the Zung Self-Rating Depression Scale has been correctly grouped by the Hospital Anxiety and Depression Scale depression subscale at a ratio of 0.848, Beck Depression Inventory at a ratio of 0.872, and by CES-Depression Scale at a ratio of 0.878. The total score of the Hospital Anxiety and Depression Scale (depression subscale) has been correctly grouped by the Zung Self-Rating Depression Scale at a ratio of 0.848, Beck Depression Inventory at a ratio of 0.889, and by CES-Depression Scale at a ratio of 0.887. Conclusion: The overall results showed that the scales cross-validated with ratios ranging from 0.85 to 0.89. The classifying ratios obtained by ROC analysis were similar across four depression scales.